Strategic and economic aspects of network sharing in FTTH/PON architectures - Juan Rendon Schneir; Yupeng Xiong (International Telecommunications Society (ITS), 2012)
Due to the high costs associated with the deployment of the passive infrastructure of FTTH networks, operators ponder the possibility of making co-investments based on a network sharing model. This article describes the strategic and economic aspects of network sharing in FTTH/PON architectures. The capabilities of present and future versions of PON architectures and the cost implications of a network sharing model are described. Moreover, the minimum price of the access line necessary to recover the investment is derived.
Keywords: 330; FTTH; cost; network sharing; PON